Chapter 1 Getting real about monogamism Disrupting mononormative bias in sex therapy and relationship counselling - Ansara, Y Gavriel (Taylor & Francis, 2023)
This chapter discusses monogamism as a type of systemic oppression enacted through ideas and practices that valorise monogamous people and relationships while systematically devaluing polyamorous and multi-partnered relationships. Instead of focusing on polyamorous/multi-partnered people, this chapter will apply the critical gaze of a sex and relationship therapist with polyamorous lived experience to examine and critique how psychotherapists behave toward polyamorous/multi-partnered people. Ansara explores how psychotherapists routinely engage in three common forms of monogamism: mononormative bias, couple-centric bias, and everyday monogamism. When examining these three forms of monogamism, Ansara explains how some ostensibly "neutral" and ubiquitous language, concepts, and clinical practices can enact monogamist oppression. This chapter then analyses how popular theoretical approaches to relationship counselling promote couple-centric bias and fail to address the key patterns, dynamics, and dilemmas in multi-partnered relationship systems. This includes an anti-racist, decolonial critique of Eurocentric approaches to Attachment Theory and the culture-bounded nature of mononormative biases. Finally, this chapter provides evidence-informed guidelines for anti-oppressive psychotherapeutic practice that can help polyamorous and multi-partnered people to strengthen attachment bonds, improve communications, and meet core emotional needs in their relational systems.